COMPETITIVE ADVANTAGE ANALYSIS: A VALUE CHAIN MODEL IN THE JEMBER CARNIVAL INDUSTRY - Subagio, N. Ari; Sukarno, Hari; Khusna, Khanifatul; Muhsyi, Abdul; Priyono, Agus (Jurnal Ilmiah Ekonomi Bisnis, 2024)
The subsector of performing arts studied in this research is in carnival performance art. The pandemic era has made the performance of all business entities decline, including in the creative industry of the performing arts subsector (Carnival). The research method used is qualitative research, namely by describing and exploring the application of value chains and culture in the creative industry of the carnival performing arts subsector in the Jember region. The data were collected through interviews, observations, and document analysis. The study concludes with the identification of the value chain sustainability model event in Jember, comprising five key elements. These elements include creation, production, dissemination, exhibition, and consumption, indicating the presence of a comprehensive value chain within the Jember Regency carnival event. Jember Carnival's one-of-a-kind creative vision woven through the entire elements, from creation to consumption, gives it a major differentiation advantage compared to standardized carnival offerings. The uniqueness provides lasting value and competitive edge. A potential chain that can be used as a source of competitive advantage for the sustainability of the Jember carnival event is to have a different creation from other carnivals.